Sustaining the S.P.A.R.K. (Supporting Parents Anticipating Resilient Kids): A study on program implementation during the transition to parenthood - Wehling, Anna J. (My University, 2025)
The intent of this study was to obtain feedback on a new and innovative intervention designed to help romantic partners sustain fulfilling relationships throughout the transition to parenthood called Sustaining the SPARK (Supporting Parents Anticipating Resilient Kids). Four formative evaluation approaches were used to assess: (a) therapists’ satisfaction with the program training, (b) the value propositions that would best motivate therapists to become trained in the program, (c) what parents of young children think is important for program effectiveness, and (d) the experiences of expectant parents going through the program. First, graduate couple and family therapy student therapists (n = 3) reported after being trained in the curriculum they were the most comfortable with the values topic of the curriculum, followed by the topics of emotion regulation and finances/financial goals, which were tied. Finally, conflict resolution, expectations, and gender roles/labor division were ranked as topics therapists were least comfortable with. All three trained therapists reported they were satisfied or very satisfied with the quality of the training in a variety of areas, but rated engagement and interactive aspects of the training the lowest, which provides a clear focus for further training improvements. Second, the market testing to 22 therapists in the K-State Couple and Family Therapy Program explored which values would be most effective in motivating therapists to enroll for training and program dissemination. The statement that included an appeal to therapists’ passion for helping couples was ranked as the most motivating. Additional qualitative feedback identified that therapists were motivated most by statements with positive language and emotional tone, and they were least motivated by statements that did not highlight their clinical interests or values (e.g., money-focused). Third, our focus group of parents with children under 4 years-old (n = 4) provided qualitative feedback on Sustaining the SPARK. Feedback revealed themes related to factors that may help participants attend and remain engaged in the program, the importance of focusing on partners’ values in the curriculum, as well as the importance of addressing real-life relationship challenges and practical applications within the curriculum. Only one couple transitioning to parenthood has enrolled in the program and data is currently being collected.
Keywords: Transition to parenthood; Pregnant couples; Program implementation